2019
DOI: 10.1158/1535-7163.mct-18-0573
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinase Signaling Networks Define Sensitivity to ERBB Inhibition and Stratify Kras-Mutant Lung Cancers

Abstract: Most non-small cell lung cancers (NSCLCs) contain non-targetable mutations, including KRAS, TP53 or STK11/LKB1 alterations. By coupling ex vivo drug sensitivity profiling with in vivo drug response studies, we aimed to identify drug vulnerabilities for these NSCLC subtypes. Primary adenosquamous carcinoma (ASC) or adenocarcinoma (AC) cultures were established from Kras G12D ;Lkb1 fl/fl (KL) tumors or AC cultures from Kras G12D ;p53 fl/fl (KP) tumors. While p53 null cells readily propagated as conventional cult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 43 publications
14
19
0
Order By: Relevance
“…1E-F), matching previous findings in CR cultures. 19 In further agreement with published data, 22,23 a synergistic interaction was detected between MEK and ERBB receptor family inhibition in KL, but not in KP FUTCs ( Fig. 2A).…”
Section: Murine Fresh Uncultured Tumor-derived Cells (Futcs) Capture supporting
confidence: 92%
See 4 more Smart Citations
“…1E-F), matching previous findings in CR cultures. 19 In further agreement with published data, 22,23 a synergistic interaction was detected between MEK and ERBB receptor family inhibition in KL, but not in KP FUTCs ( Fig. 2A).…”
Section: Murine Fresh Uncultured Tumor-derived Cells (Futcs) Capture supporting
confidence: 92%
“…1D and F), corroborating findings from cultured lung cancer models. [19][20][21] Lastly, we confirmed that gemcitabine, an approved chemotherapeutic agent for NSCLC treatment, potently inhibited the viability of both KL and KP cells ( Fig. 1E-F), matching previous findings in CR cultures.…”
Section: Murine Fresh Uncultured Tumor-derived Cells (Futcs) Capture supporting
confidence: 89%
See 3 more Smart Citations